2018
DOI: 10.1016/j.foodchem.2018.06.081
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic profile and bioactivity of cardoon (Cynara cardunculus L.) inflorescence parts: Selecting the best genotype for food applications

Abstract: This study was designed to characterize the phenolic profile and bioactivity of hydroalcoholic extracts from different cardoon (Cynara cardunculus L.) genotypes. The analytical work focussed on the inflorescence stigmas, owing to their application in cheese production. Nevertheless, other parts were concomitantly analysed aiming to define their possible use in related applications. Phenolic profiles obtained by LC-DAD-ESI/MSn showed significant differences among different cardoon genotypes, but apigenin and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
53
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 35 publications
5
53
2
Order By: Relevance
“…As far as the author's knowledge, the antibacterial activity of the aerial parts of turnip and radish have not been reported. However for wild cardoon, previous studies reported good antibacterial activity in other parts of wild cardoon, thus also bio-wastes (Dias et al, 2018). Kukić et al (2008) reported lower MIC values in the hydroethanolic and aqueous extracts of fresh involucre bracts of cardoon from Bratislava against E. coli and Staphylococcus aureus (1.0 mg/mL and 1.5 mg/ mL, respectively); however is important to state that the bacteria strains used were ATCC, which present a lower resistance profile when compared to the ones studied herein (clinical isolates with high resistance profile).…”
Section: Bioactivity Of the Hydroethanolic And Infusion Extractsmentioning
confidence: 94%
See 1 more Smart Citation
“…As far as the author's knowledge, the antibacterial activity of the aerial parts of turnip and radish have not been reported. However for wild cardoon, previous studies reported good antibacterial activity in other parts of wild cardoon, thus also bio-wastes (Dias et al, 2018). Kukić et al (2008) reported lower MIC values in the hydroethanolic and aqueous extracts of fresh involucre bracts of cardoon from Bratislava against E. coli and Staphylococcus aureus (1.0 mg/mL and 1.5 mg/ mL, respectively); however is important to state that the bacteria strains used were ATCC, which present a lower resistance profile when compared to the ones studied herein (clinical isolates with high resistance profile).…”
Section: Bioactivity Of the Hydroethanolic And Infusion Extractsmentioning
confidence: 94%
“…Finally, luteolin (peaks 7 CC and 11 CC ) and apigenin (peaks 12 CC ) derivatives were only found in wild cardoon leaves. Peak 7 CC , tentatively identified as luteolin-O-hexoside, presented a pseudomolecular ion [M-H] − at m/z 447 and a unique MS 2 fragment at m/z 285 (162 mu); while peak 11 CC |([M-H] − at m/z 533) was tentatively identified as luteolin-O-malonylhexoside, presenting MS 2 fragments at m/z 489 ([M-H-44] − ) and at m/z 285 ([M-H-42-162] − ), that corresponded to the loss of the malonyl moiety (86 mu) and the hexosyl moiety (Dias et al, 2018). Peak 12 CC ([M-H] − at m/z 473) was tentatively identified as acetylapigenin-O-hexoside presenting a unique MS 2 fragment at m/z 269, corresponding to the loss acetyl and hexosyl moieties, respectively.…”
Section: Phenolic Profile Of the Hydroethanolic Extract And Infusionmentioning
confidence: 99%
“…In the inflorescence, the bracts (7497.7 mg kg −1 dw) showed a clearly prevalence comparing with the receptacle (1102 mg kg −1 dw) . Both 1,3‐ and 1,5‐ O ‐dicaffeoylquinic acid were identified in wild cardoon, and also in cardoon flowers . Additionally, 1,4‐ O ‐dicaffeoylquinic acid only was found in cultivated cardoon .…”
Section: Bioactive Compoundsmentioning
confidence: 95%
“…Six dicaffeoylquinic acids, namely 1,3‐, 1,4‐, 1,5‐, 3,4‐, 3,5‐, and 4,5‐ O ‐dicaffeoylquinic acids, were detected, simultaneously, in artichoke leaves, stalks and capitula . Cynarin (1,3‐ O ‐dicaffeoylquinic acid), one of the phenolic compounds with highest concentration, is mainly present in flowers (1.7–2.4 mg g −1 ), followed by leaves (465.5 mg kg −1 dw), stems (90.2 mg kg −1 dw), and inflorescences (73.4 mg kg −1 dw) . 1,5‐ O ‐dicaffeoylquinic acid was the second most abundant caffeoylquinic acid (21 %) with the highest concentration in artichoke inflorescences (28788 mg kg −1 fw; 7498 mg kg −1 dw), followed by the stem (6363 mg kg −1 dw) and leaves (6833 mg kg −1 fw) .…”
Section: Bioactive Compoundsmentioning
confidence: 99%
See 1 more Smart Citation